Economic thought and policy in the Liberal Party, c. 1929-1964 - Sloman, PJ (2013)
This thesis examines the reception, generation, and use of economic ideas in the British Liberal Party during the period between its decline in the inter-war years and its revival under Jo Grimond. It uses archival sources, party publications, and the political press to reconstruct the Liberal Party’s internal discourse about economic policy from the 1920s to the 1960s, and sets this discourse in the context of wider economic and political developments: the ‘Keynesian revolution’ in economic theory and British public policy, recurrent political interest in economic planning, and growing concern about relative economic decline. The strength of the two-party system which developed after the First World War meant that the Liberal Party spent most of this period in opposition, and even in the coalition governments of 1931-2 and 1940-5 Liberals had limited input into economic policy-making. As historians have frequently noted, however, the party played an important role in introducing Keynesian ideas to British politics through Lloyd George’s 1929 pledge to ‘conquer unemployment’, and seemed to anticipate the post-war managed economy in important respects. At the same time, the party maintained a close relationship with the economics profession, and vocally championed free trade and competitive markets. This thesis highlights the eclecticism of the Liberal Party’s economic heritage, and its continuing ambivalence towards state intervention. Although Liberals were early and sincere supporters of Keynesian demand-management policies, and took a close interest in economic planning proposals in the 1920s, 1940s and 1960s, their interventionism was frequently constrained by their internationalism and their support for free markets. Most Liberals, then, were neither unreconstructed Gladstonians nor unequivocal supporters of Britain’s post-war settlement. Rather, successive party leaders sought to integrate new economic knowledge with traditional Liberal commitments, in order to make both a credible contribution to policy debates and a distinctive appeal to the electorate.